Current status of preoperative drainage for distal biliary obstruction - Sugiyama, Harutoshi (World J Hepatol, 2015)
Preoperative biliary drainage (PBD) was developed to improve obstructive jaundice, which affects a number of organs and physiological mechanisms in patients waiting for surgery. However, its role in patients who will undergo pancreaticoduodenectomy for biliary obstruction remains controversial. This article aims to review the current status of the use of preoperative drainage for distal biliary obstruction. Relevant articles published from 1980 to 2015 were identified by searching MEDLINE and PubMed using the keywords “PBD”, “pancreaticoduodenectomy”, and “obstructive jaundice”. Additional papers were identified by a manual search of the references from key articles. Current studies have demonstrated that PBD should not be routinely performed because of the postoperative complications. PBD should only be considered in carefully selected patients, particularly in cases where surgery had to be delayed. PBD may be needed in patients with severe jaundice, concomitant cholangitis, or severe malnutrition. The optimal method of biliary drainage has yet to be confirmed. PBD should be performed by endoscopic routes rather than by percutaneous routes to avoid metastatic tumor seeding. Endoscopic stenting or nasobiliary drainage can be selected. Although more expensive, the use of metallic stents remains a viable option to achieve effective drainage without cholangitis and reintervention.